Maternal Death in Rural Ghana: A Case Study in the Upper East Region of Ghana - Apanga, Paschal Awingura; Awoonor-Williams, John Koku (Frontiers in Public Health, 2018)
Maternal mortality remains a challenge in providing quality maternal and other reproductive healthcare services in Ghana. This is a case investigation of a maternal death in rural Ghana that seeks to unravel the circumstances that lead to her death. We conducted three in-depth interviews with healthcare staff as well as a focused group discussion comprising of six relatives of the deceased, including her husband. The investigation revealed that lack of logistics, medical, and laboratory equipment, inadequate knowledge about the benefits of antenatal care services as well as non-adherence of healthcare workers to treatment protocols and standard operating procedures were found as major setbacks to the provision of effective and quality maternal healthcare services in Ghana. It is, therefore, imperative for the Government of Ghana and other Non-Governmental Organizations to invest in strengthening the healthcare delivery system especially in rural Ghana by making available basic logistics, medical, and laboratory equipment, as well as improving upon maternal health education, and consistently organizing capacity building training programs for healthcare workers.